Implementasi Pembelajaran Berdiferensiasi Kurikulum Merdeka pada Mata Pelajaran Matematika Kelas IV SDN Bacem - Ni’am Nur Wafa’; Ibadullah Malawi; Sukarmi Sukarmi (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
An action that results in the existence of several planned activities and actions taken to accomplish a goal is called implementation. A set or system of plans and arrangements relating to educational resources that can direct teaching and learning activities is called a curriculum. With a variety of intracurricular learning opportunities, the independent curriculum allows students to freely study all the material and facilitates the development of deeper concepts. The purpose of this study is to: (1) Determine how differentiated learning is implemented in SDN Bacem's grade IV mathematics classes, (2) To determine the elements that facilitate and hinder the use of differentiated instruction in the autonomous curriculum for SDN Bacem's grade IV mathematics courses. This researcher does field research using a descriptive qualitative methodology. The study's findings demonstrate that: (1) Three crucial learning components of differentiated learning the content/content element, the process aspect, and the product aspect are applied in this autonomous curriculum. (2) Learning materials such as books and learning media are available to promote differentiated learning. Additionally, there are other constraints that hinder varied learning, such as a lack of infrastructure and resources and instructors' limited time to execute it.